2013
DOI: 10.1007/s00403-013-1321-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic staging of cutaneous malignant tumors: an ultrasonographic depth index

Abstract: The objective of this paper is to assess the role of conventional and high-frequency ultrasound in the evaluation of the depth of cutaneous skin cancer. The study was performed on 46 subjects, divided into 3 categories, according to their skin pathology [basal cell carcinoma (BCC), 18 subjects; superficial spreading melanoma (SSM), 8 subjects; nodular melanoma (NM), 20 subjects]. Conventional and high-frequency ultrasonographic measurements were performed in order to assess the thickness of the tumors and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 27 publications
3
123
1
12
Order By: Relevance
“…Reduced elasticity correlates with tumour congestion and hypervascularization [6][7][8]. This case report emphasizes the importance of US in evaluating cutaneous tumours and its impact on therapeutic approach optimisation.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Reduced elasticity correlates with tumour congestion and hypervascularization [6][7][8]. This case report emphasizes the importance of US in evaluating cutaneous tumours and its impact on therapeutic approach optimisation.…”
Section: Introductionmentioning
confidence: 68%
“…Increased sonographic index values in comparison to the histological Breslow index values in our case can be explained by the presence of the peritumoral inflammatory infiltrate. In addition, according to the literature data and our experience, the high frequency ultrasound (Dermascan 20MHz) offers highly accurate depth index information in comparison to conventional US [8,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method should be used as a complementary method in preoperative evolution of the tumor. [47][48][49] Wortsman et al, in a large retrospective study of 4338 ultrasonographic skin examinations, showed that the addition of HF ultrasonography increased the correctness of clinical diagnosis from 73% to 97%. …”
Section: High Frequency Ultrasonographymentioning
confidence: 99%
“…The highest resolution high-frequency ultrasound devices (20-100 MHz) showed a 99.4% correlation with pathology in an analysis of superficial spreading melanoma. 40 Jasaitiene et al indicate that the correlation between the thickness of melanoma assessed by ultrasound examination and histopathological examination in the case of devices with a frequency of 20, 75 and 100 MHz is from 0.895 to 0.99, whereas for the devices of 7.5 MHz the "r" value is 0.76. 38 …”
Section: High Frequency Ultrasonographymentioning
confidence: 99%